REDESCRIPTION OF OSCHIOUS SP. AROUND SUGARCANE SOIL IN OSMANABAD DISTRICT(M.S) INDIA. - DALVE , KOMAL; BORDE, SUNITA (The Bioscan, 2023)
Redescription of the genus, Oschious was found in the soil around root of sugarcane crops in Osmanabad district (M. S) India. Molecular and morphological analysis were performed. The species is characterized by body size medium and length measures 2587mm, a = 18.9, b = 3.43, c = 19.9, c’= 1.66, V=55.62%Length of stoma 65µm.Amphids circular, female reproductive system amphidelphic and pointed tail.